NILAI-NILAI KEARIFAN LOKAL LUWU DALAM PENDIDIKAN ANTI KORUPSI DI MADRASAH ALIYAH NEGERI PALOPO - Muhaemin Muhaemin; Muhadir Azis (Balai Penelitian dan Pengembangan Agama Makassar, 2019)
This research aims to examine the form of Luwu's local value-relevance in anti-corruption education, madrasa efforts in instilling Luwu's local wisdom values in anti-corruption education, teacher's strategy in instilling Luwu's local wisdom values in Anti-corruption education in State Madrasah Aliyah Palopo using descriptive qualitative methods. Data sources used primary data from principals, vice principals and teachers of moral akidah, Al-Qur'an hadith, and PKn as well as students through interviews, while secondary data from school documents. The instrument is the researcher himself who collects and selects informants as sources of data, analyzes data, and manages data. Supporting instruments for observation sheets, interview sheets, cameras, recorders, and stationery. The results of the study show that, the relevance of local wisdom in anti-corruption education in the assessment of educational values with the creation of a religious atmosphere in the madrasa environment.